Implementasi Pada Kehamilan Dengan Hipertensi Kronis Superimposed Preeklampsia - Wahyu Nuraisya (Jurnal Vokasi Kesehatan, 2023)
Preeclampsia is a disorder that occurs in pregnant women and is a leading cause of maternal and perinatal mortality and morbidity up to fivefold after bleeding and infection. The research approach / design that has been carried out is a case study. Research has been conducted to determine the proper implementation of Mrs. J pregnant women at UPTD Puskesmas Plosoklaten Kediri Regency. The method of data collection that has been carried out is by means of anamnesis / interview, observation and documentation (SOAP). The review and implementation will be carried out in January 2023 in the MCH room. The results of the data collection of mothers complained of frequent dizziness, had a history of hypertension from biological mothers and currently Mrs.J suffers from chronic hypertension. History of previous childbirth by means of Sectio Caesarea (SC). Blood Pressure Results 140/80 mmHg, TD tilted: 120/60 mmHg, ROT 20 (positive), MAP 100 (positive), lila 23 cm and KSPR 18 (pregnant, SC, hypertension, distance between children 2 years). On the lower extremities there is oedema of the right and left legs. Fetal Heart Rate auscultation examination is 144 x / m, regular, strong. Based on the results of subjective data and objective data, analysis. Mrs. J is G2P1A0 gestational age 23-24 weeks single/live/intrauterine fetus, KU mother and fetus are both with chronic hypertension superimposed preeclampsia. The implementation given to Mrs. J G2P1A0 UK 23-24 weeks with chronic hypertension superimposed preeclampsia was carried out comprehensively and SOP for pregnancy check. Midwives have conducted initial screening and advised patients to check with doctors for therapy and make planned early referrals to prevent complications in mothers and babies.